PENDAPATAN DAN KESEJAHTERAAN PETANI PADI ORGANIK PESERTA SEKOLAH LAPANGAN PENGELOLAAN TANAMAN TERPADU (SL-PTT) DI KECAMATAN PAGELARAN KABUPATEN PRINGSEWU - Putri, Tika Leoni; Hepiana Lestari, Dyah Aring; Nugraha, Adia (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2013)
The purposes of this research were to determine the level of income and profits of organic rice farming SL-PTT participants, determine the level of household income SL-PTT participants, determine the level of welfare household SL-PTT participants in the District of Pagelaran of Pringsewu Regency. This research was conducted in Pagelaran and Gemah Ripah villages of Pagelaran District. The research samples were drawn from the population by simple random design. The total samples were 77 farmers consisted of 37 SL-PTT participants and 40 SL-PTT non-participants. The data was analyzed by farm income analysis, household income analysis and welfare analysis based on Sajogyo’s criteria (1997). The results showed that the average of income SL-PTT participants based on cash costs and total cost were Rp11,510,16.35 dan Rp13,047,112.84 and acceptance ratios obtained by cost (R/C ratio) in cash and in total were 4.69 and 3.27. Average income of SL-PTT non participants based on cash costs and total cost were Rp9,803,268.59 and Rp8,418,819.09 and acceptance ratios obtained by cost (R/C ratio) and total cash were 3.7 and 2.68. Averages household income of SL-PTT participants was Rp39,174,915.54 per year. Averages household income of SL-PTT non-participants was Rp36,978,219 per year. Based on Sajogyo’s criteria, there was one of household SL-PTT paricipant that was classified as moderate household and three of household SL-PTT non participants were classified as moderate household. Keywords: household, income, organic rice, SL-PTT, welfare